Detailed genetic mapping of the von Hippel-Lindau disease tumour suppressor gene. Issue 2 (February 1993) - Richards, F M; Maher, E R; Latif, F; Phipps, M E; Tory, K; Lush, M; Crossey, P A; Oostra, B; Enblad, P; Gustavson, K H
Abstract : Von Hippel-Lindau (VHL) disease is an autosomal dominant inherited familial cancer syndrome characterised by a predisposition to the development of retinal, cerebellar, and spinal haemangioblastomas, renal cell carcinoma, and phaeochromocytoma. The gene for VHL disease has been mapped to chromosome 3p25-p26 and flanking markers identified. We report the detailed genetic mapping of the VHL disease locus in 38 families. Significant linkage was detected between VHL disease and D3S601 (Zmax = 18.86 at theta = 0.0, CI 0.0-0.025), D3S18 (Zmax = 11.42 at theta = 0.03, CI 0.005-0.08), RAF1 (Zmax = 11.02 at theta = 0.04, CI 0.007-0.01), and D3S1250 (Zmax = 4.73 at theta = 0.05, CI 0.005-0.15). Multipoint linkage analysis mapped the VHL disease locus between D3S1250 and D3S18 close to D3S601. There was no evidence of locus heterogeneity. This study has (1) confirmed the tight linkage between VHL disease and D3S601, (2) identified D3S1250 as the first marker telomeric to RAF1 which maps centromeric to the VHL disease gene, and (3) narrowed the target region for isolation of the VHL disease gene by positional cloning techniques to a 4 cM interval between D3S1250 and D3S18. These findings will improve the clinical management of families with VHL disease by improving the accuracy of presymptomatic diagnosis using linked DNA markers, and will enhance progress towards isolating the VHL disease gene.